2017
DOI: 10.1002/jgm.2947
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress gene polymorphisms may have an impact in the development of ischemic stroke

Abstract: It is unlikely that CAT and GPX1 single nucleotide polymorphisms are risk factors for IS. The results of the present study show that smoking may be a risk factor for IS risk in patients with MnSOD mutant genotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Sharma et al found that Gpx1 silencing promoted the proinflammatory response and activated vascular endothelium [ 19 ]. Moreover, Karahalil et al reported that Gpx1 served as a risk factor for ischemic stroke [ 20 ], indicating that Gpx1 might be involved in the development of ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma et al found that Gpx1 silencing promoted the proinflammatory response and activated vascular endothelium [ 19 ]. Moreover, Karahalil et al reported that Gpx1 served as a risk factor for ischemic stroke [ 20 ], indicating that Gpx1 might be involved in the development of ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the following three co-variables were also considered despite a lack of specific associative studies between them and Val16Ala-SOD2 polymorphism: hypertension, smoking, and polypharmacy. Previous reports describe an association between the Val16Ala-SOD2 SNP and cardiovascular diseases (Flores et al, 2017;Fujimoto, Kobayashi, Ogasawara, Yamakado, & Ohno, 2010;Fujimoto et al, 2008;Kakko et al, 2003;Karahalil, Elkama, & Orhan, 2017;Souiden et al, 2016), for which hypertension and smoking habits are important risk factors. Regarding polypharmacy, consistent evidences exist supporting an association between certain pharmacological drugs and body weight modulation, including antidepressants (Abosi, Lopes, Schmitz, & Fiedorowicz, 2018) and antipsychotic drugs, which are sometimes prescribed to depressive elderly patients (Dayabandara et al, 2017).…”
Section: Case-control Protocolmentioning
confidence: 99%
“…GPX1 and MnSOD are located on chromosomes 3p21 and 6q25, respectively. Commonly studied genetic polymorphisms on these enzymes are GPX1 Pro198Leu and MnSOD Ala16Val , and these gene polymorphisms may decrease MnSOD and GPX1 activities; so they possibly increase susceptibility to oxidative stress 25 . For the XRCC1 enzyme, which is thought to be effective in neurological disorders, three most widely studied polymorphisms have been identified and may be functionally relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly studied genetic polymorphisms on these enzymes are GPX1 Pro198Leu and MnSOD Ala16Val, and these gene polymorphisms may decrease MnSOD and GPX1 activities; so they possibly increase susceptibility to oxidative stress. 25 For the XRCC1 enzyme, which is thought to be effective in neurological disorders, three most widely studied polymorphisms have been identified and may be functionally relevant. Of the three polymorphisms, it was shown that XRCC1 Arg399Gln might reduce the efficiency of the repair process by changing a conserved amino acid in the binding domain of PARP or polynucleotide kinase (PNK).…”
mentioning
confidence: 99%